The mitochondrial genome of the orange-striped green sea anemone Diadumene lineata (Actiniaria: Diadumenidae): the first complete sequence in the family Diadumenidae. Issue 1 (2nd January 2020) - Cong, Haiyan; Lei, Yixuan; Kong, Lingming
Abstract: The complete mitogenome of the orange-striped green sea anemone ( Diadumene lineata ) has been sequenced and annotated for the first time. The total length of the mitogenome is 17, 552 bp with an A+T content of 62.6%. Unlike typical metazoan mitogenome, this mitogenome include 14 protein-coding genes (13 energy pathway protein coding genes, and a heg gene), two tRNAs, two rRNAs, and 19 intergenic regions. The COX1 gene possesses a homing endonuclease gene. This circular genome contains two introns, one in ND5 and another in COX1.This sequence is the first sequenced complete mitogenome in Diadumenidae and provides fundamental data for exploring complicated evolutionary relationships in Actiniaria.